Tales from long ago and why we need them to secure a resilient today - Harini Nagendra, Hita Unnikrishnan, B. Manjunatha, (Universitas Andalas, 2015)
We live in the Anthropocene, at a time when the human footprint is at its most pronounced. In the process ofrapid urbanization, that characterizes today's age, many ecological commons with complex histories ofgovernance and stewardships are reimagined in keeping with prevailing notions of their utility. This redefining of acommon often occurs in exclusion of former social and cultural relationships built around the resource leading toentire communities being disconnected from it. The resultant loss of perceived value can enhance vulnerability tothreats including a loss of its identity as an ecological common. In this paper, we use the case of a former lake (Sampangi lake) within the south Indian city of Bengaluru toillustrate what makes understanding the past so important when it comes to management of urban ecologicalcommons. The Sampangi lake, now a major sports stadium of the city, was once an important ecological, social,and cultural resource. Besides being an indispensable water source to the city up until the mid-19th century, thelake also supported various other forms of provisioning and cultural ecosystem services – ranging across servingdomestic purposes, livelihoods, and belief systems. How then did this lake fade into obscurity and eventualoblivion in the intervening years, and more importantly, what happened to the people who once had strong ties withthe resource? Do events of long ago resonate even today and if so, how do they still speak to us? In order to answer these questions, we combine landscape change analysis through geospatial methodsalong with official archival records and oral narratives to unravel the story of change and its impacts on this urbancommon. We examine different changing notions of the utility of this lake pictured against a backdrop of rapidurbanization, migration, and landscape change. We relate this historical picture with contemporary trends in lakemanagement to draw a parallel. In so doing, we demonstrate that obtaining knowledge about the history of aresource, the history of its use, the various stakeholders accessing it, and the various conflicts it witnessed can helpprevent exclusionary histories, alienation of communities, and encourage citizen stewardship of the resource. Thiscan further shape more equitable, ecologically robust policy frameworks aimed at enhancing social and ecologicalresilience and therefore longevity of the resource.